2014
DOI: 10.3390/jmse2010123
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Site Model for Newark Bay—Hydrodynamics and Sediment Transport

Abstract: A conceptual site model (CSM) has been developed for the Newark Bay Study Area (NBSA) as part of the Remedial Investigation/Feasibility Study (RI/FS) for this New Jersey site. The CSM is an evolving document that describes the influence of physical, chemical and biological processes on contaminant fate and transport. The CSM is initiated at the start of a project, updated during site activities, and used to inform sampling and remediation planning. This paper describes the hydrodynamic and sediment transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Pecchioli et al (2006) estimated approximately 100,000 MT/year of suspended sediment through Kill van Kull. Chant (2006) reported transport of between 120,000 and 200,000 MT/year using data collected in 2002, and Shrestha et al (2014) reported Kill van Kull transport of 140,000 MT/year. This indicates an acceptable range of approximately 100,000 MT/year to 200,000 MT/year, although this would vary depending on the Hudson River flow conditions.…”
Section: Kill Van Kull Sediment Loadsmentioning
confidence: 99%
“…Pecchioli et al (2006) estimated approximately 100,000 MT/year of suspended sediment through Kill van Kull. Chant (2006) reported transport of between 120,000 and 200,000 MT/year using data collected in 2002, and Shrestha et al (2014) reported Kill van Kull transport of 140,000 MT/year. This indicates an acceptable range of approximately 100,000 MT/year to 200,000 MT/year, although this would vary depending on the Hudson River flow conditions.…”
Section: Kill Van Kull Sediment Loadsmentioning
confidence: 99%
“…Because of its limited freshwater inflow, the lower Hackensack River is susceptible to local pollution sources, which have collectively degraded water quality and sediment quality [16]. In contrast, the concentrations of nutrients were relatively lower in the Passaic River than in the Hackensack River, probably because of faster draining of combined sewer overflows into the Newark Bay due to higher freshwater discharge in the Passaic River than in the Hackensack River [12].…”
Section: Spatial Variations Of Water Quality In the Newark Bay Estuarymentioning
confidence: 99%
“…Volgens een studie van Cloern et al (2017) ("non-cohesive"). C is het gesuspendeerde sediment profiel, U is de stroomsnelheid, τb schuifspanning en u* is de schuifsnelheid (Shrestha, Su et al 2014). …”
Section: Estuariene Circulatie En Stratificatieunclassified